Reverse Engineering 3D Printing Innova Big Print - Zainuddin, Zainuddin; Widiantoro, Heri; Pamungkas, Adi; Rachmat, Angki Apriliandi (Suara Teknik : Jurnal Ilmiah, 2024)
3D Printing is the process of creating 3D objects from CAD models. 3D printing technology is used to make various objects ranging from toys to components on machines. The advantages of this method allow the manufacture of prototypes at low cost and shorter processing time than other methods. Reverse engineering is the process of analyzing existing products as a reference to design similar products by minimizing and increasing product advantages. With the reverse engineering method, the performance principle of a tool, object, or system can be done by analyzing its structure, function, and operation. The purpose of this research is to be able to redesign the 3D Printing Machine so that students and lecturers can transfer technology and maintain in the development of 3D Printing machines made by domestic children. The output in this study is a 3D Printing machine that can operate with an area of 500x500 mm. The results of this study include, 1). This Innova Big Print 3D Printing Machine can be developed and upgraded into a Reliable 3D Machine. 2).This 3D machine can be increased in speed from 60 mm/s to 120 mm/s, This has experienced a very significant increase. 3). This 3D Print machine can already transfer data using wifi so that it makes it easier in the printing process.